Proteomic profiling of formalin-fixed paraffine-embedded tissue reveals key proteins related to lung dysfunction in idiopathic pulmonary fibrosis - Samarelli, Anna Valeria; Tonelli, Roberto; Raineri, Giulia; Bruzzi, Giulia; Andrisani, Dario; Gozzi, Filippo; Marchioni, Alessandro; Costantini, Matteo; Fabbiani, Luca; Genovese, Filippo; Pinetti, Diego; Manicardi, Linda; et al. (Frontiers in Oncology, 2024)
Idiopathic pulmonary fibrosis (IPF) severely affects the lung leading to aberrant deposition of extracellular matrix and parenchymal stiffness with progressive functional derangement. The limited availability of fresh tissues represents one of the major limitations to study the molecular profiling of IPF lung tissue. The primary aim of this study was to explore the proteomic profiling yield of archived formalin-fixed paraffin-embedded (FFPE) specimens of IPF lung tissues. We further determined the protein expression according to respiratory functional decline at the time of biopsy. The total proteins isolated from 11 FFPE samples of IPF patients compared to 3 FFPE samples from a non-fibrotic lung defined as controls, were subjected to label-free quantitative proteomic analysis by liquid chromatography-mass spectrometry (LC-MS/MS) and resulted in the detection of about 400 proteins. After the pairwise comparison between controls and IPF, functional enrichment analysis identified differentially expressed proteins that were involved in extracellular matrix signaling pathways, focal adhesion and transforming growth factor β (TGF-β) signaling pathways strongly associated with IPF onset and progression. Five proteins were significantly over-expressed in the lung of IPF patients with either advanced disease stage (Stage II) or impaired pulmonary function (FVC<75, DLco<55) compared to controls; these were lymphocyte cytosolic protein 1 (LCP1), peroxiredoxin-2 (PRDX2), transgelin 2 (TAGLN2), lumican (LUM) and mimecan (OGN) that might play a key role in the fibrogenic processes. Our work showed that the analysis of FFPE samples was able to identify key proteins that might be crucial for the IPF pathogenesis. These proteins are correlated with lung carcinogenesis or involved in the immune landscape of lung cancer, thus making possible common mechanisms between lung carcinogenesis and fibrosis progression, two pathological conditions at risk for each other in the real life. Formattato: Italiano (Italia) Codice campo modificato Codice campo modificato Codice campo modificato Formattato: Italiano (Italia) Codice campo modificato